2017
DOI: 10.1038/srep43684
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor-1 activates autophagy to aggravate hepatic ischemia-reperfusion injury via the P38/P62 pathway in mice

Abstract: Increasing evidence has linked autophagy to a detrimental role in hepatic ischemia- reperfusion (IR) injury (IRI). Here we focus on the role of interferon regulatory factor-1 (IRF-1) in regulating autophagy to aggravate hepatic IRI. We found that IRF-1 was up-regulated during hepatic IRI and was associated with an activation of the autophagic signaling. This increased IRF-1 expression, which was allied with high autophagic activity, amplified liver damage to IR, an effect which was abrogated by IRF-1 depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Our previous research was directed toward examining the role of IRF-1 in regulating autophagy to aggravation on hepatic IRI as coupled with IRF-1. We also found that IRF-1 was up-regulated during hepatic IRI and was associated with an activation of the autophagic signaling [17]. In this study, we report that IRF-1 was …”
Section: Discussionsupporting
confidence: 57%
“…Our previous research was directed toward examining the role of IRF-1 in regulating autophagy to aggravation on hepatic IRI as coupled with IRF-1. We also found that IRF-1 was up-regulated during hepatic IRI and was associated with an activation of the autophagic signaling [17]. In this study, we report that IRF-1 was …”
Section: Discussionsupporting
confidence: 57%
“…Each sample was blindly analyzed to measure the extent of liver damage based on the technique outlined by Yu et al 43 Briefly, 24 regions of the liver were graded for the degree of injury based on each of the following parameters: cytoplasmic discoloration, vacuolation formation, nuclear pyknosis, nuclear fragmentation, nuclear discoloration and red cell stasis. Specifically, one whole deep coronal section was …”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…43 Blood was collected after reperfusion for 12 h and centrifuged at 3,600× g for 15 min to get the sera, following which AST and ALT activities were measured by a standard automatic biochemistry analyzer.…”
Section: Liver Function Assessmentmentioning
confidence: 99%
“…However, we also found that GPR30 activation did not affect the AKT/mTOR, ERK/mTOR, and JNK‐MAPK signaling pathways. p38 MAPK is an mTOR‐independent signaling pathway that has been shown to participate in autophagy (Henson et al, ; Zhong et al, ), with p38 MAPK upregulation inducing autophagy (Matsuzawa et al, ; Qin et al, ; Yu et al, ). Our data revealed that GPR30 activation enhanced p38 phosphorylation in glutamate‐activated astrocytes, indicating that GPR30 activation restored autophagy to basal levels by modulating the p38 MAPK signaling pathway (Figure ).…”
Section: Discussionmentioning
confidence: 99%